Identification of gene expression location of angiotensin‐converting enzyme‐2 SNPs as a receptor for SARS‐CoV‐2 in different populations by using various databases - Dyah Aryani Perwitasari; Rita Maliza; Bayu Tri Murti; Haafizah Dania; Athika Darumas Putri (Universitas Gadjah Mada, 2021)
The World Health Organization (WHO) has announced that Severe Acute Respiratory Syndrome Coronavirus‐2 (SARS‐CoV‐2) and Coronavirus disease (COVID‐19) is considered a worldwide pandemic. Rapidly rising numbers of patients have been reported in almost every country, along with the growing mortality rates. Uncontrolled growth in patient numbers may be due to reasons such as treatment options and vaccine availabilities and unidentified targets of SARS‐CoV‐2. Previous study has revealed that the molecular target of SARS‐CoV‐2 is analogous to SARS (2003), i.e. angiotensin‐converting enzyme‐2 (ACE‐2). Therefore, the determination of ACE‐2 may enrich existing information and facilitate development of drugs targeted toward SARS‐CoV‐2. This study aims to screen the expression of ACE‐2 genes and their relationship to the types of SNP variants in SARS‐CoV‐2. We explored a series of observations using powerful databases, e.g. GTEx portal, HaploReg, 1000 Genome and Ensembl, to identify the gene variant of ACE‐2. We showed that ACE‐2 is highly expressed in the testes and small intestine, while its lowest level is observed in lymphocytes. Subsequently, we observed 17 gene variants containing a missense mutation potentially damaging protein level. Among these genes, single nucleotide polymorphism (SNP) rs370187012 shows the highest damage‐level score, while the lowest effect is in SNP rs4646116. The highest frequency of the C allele was observed in European populations (1%). In addition to showing that ACE‐2 is expressed in several organs, we concluded that the ACE‐2 gene variation can be found in African, American, Southeast and East Asian, and European populations. The polymorphisms of ACE‐2 impact on the ACE2 protein structure and the binding capacity of the ACE‐2 receptor with the S‐Protein of SARS‐CoV‐2.